Academic mobility through the prism of the system of international relations: Kazakhstan dimension (International relations and international law Journal, 2021)
Higher international education in international relations has acquired an important place and mode as an apparatus of soft power latterly. Situation of today the pandemic and the massive transition to a remote regime, give us enough reasons to consider many spheres of life in greater depth.The purpose of the study in this article is to define the role of academic mobility as a soft power tool in the system of international relations on the basis of a survey of participants in academic mobility.Methods and approaches. The methodological basis of the study was based on general theoretical framework, the principle of consistency and the Google Form Survey.Results and findings: a survey was conducted among participants of academic mobility; trends in academic mobility was defined; the impact of the pandemic on traditional academic mobility was analyzed.Conclusion and practical significance: The role of international higher education in international relations is shown through the use of academic mobility as a soft power tool. The analysis carried out in the article revealed that the topic of higher international education as one of the soft power apparatus for external policy strategies is at the beginning of its development trajectories in the theory of international relations. This study may be used to incorporate certain provisions into the Foreign Policy Strategy of the Republic of Kazakhstan.Key words: soft power, international higher education, academic mobility, virtual academic mobility, Kazakhstan.